Joint attention communication and other minds : issues in philosophy and psychology - Eilan, Naomi. (Clarendon Press ; New York : Oxford University Press, 2005)
"This book contains research into the cognitive phenomenon of 'joint attention'. Philosophical and psychological perspectives on the nature and significance of this phenomenon are examined"--Provided by publisher.